Semaphorin3B Promotes Proliferation and Osteogenic Differentiation of Bone Marrow Mesenchymal Stem Cells in a High-Glucose Microenvironment - Quan Xing; Jingyi Feng; Xiaolei Zhang (Stem Cells International)
Bone marrow mesenchymal stem cells (BMSCs) play an essential role in osteogenesis and bone metabolism and have already been recognized as one of the most popular seed cells for bone tissue engineering for bone diseases. However, high-glucose (HG) conditions in type 2 diabetes mellitus (T2DM) exert deleterious effects on BMSC proliferation and osteogenic differentiation. Semaphorin 3B (Sema3B) increases osteoblast differentiation in bone metabolism. Here, we determined the role of Sema3B in the proliferation and osteogenic differentiation of BMSCs in the HG microenvironment. The HG microenvironment decreased Sema3B expression in BMSCs. Moreover, HG inhibited BMSC proliferation. Furthermore, HG inhibited osteogenic differentiation in BMSCs by decreasing the expression of bone formation markers, alkaline phosphatase (ALP) activity, and mineralization. However, the administration of recombinant Sema3B reversed all of these effects. Moreover, our study found that Sema3B could activate the Akt pathway in BMSCs. Sema3B rescues defects in BMSC proliferation and osteogenic differentiation in the HG microenvironment by activating the Akt pathway. These effects were significantly reduced by treatment with an Akt inhibitor. Together, these findings demonstrate that Sema3B promotes the proliferation and osteogenic differentiation of BMSCs via the Akt pathway under HG conditions. Our study provides new insights into the potential ability of Sema3B to ameliorate BMSC proliferation and osteogenic differentiation in an HG microenvironment.